Structural Relationships among Executive Functions and Behavioral Brain Activities with Social Skills of Children with Autism: The Mediating Role of Cognitive Emotion Regulation Strategies - Ershadi Manesh, Soudabeh (Health Nexus, 2026)
The purpose of this applied study was to determine the extent of the relationship between executive functions and behavioral brain activities with the social skills of children with autism, mediated by cognitive emotion regulation strategies. In terms of purpose, the study was applied, and in terms of method and nature, it was a descriptive–correlational study using structural equation modeling. The statistical population consisted of children diagnosed with autism at the Tehran Autism Center. Based on Green’s formula, 235 questionnaires were distributed among the sample using non-random purposive sampling. Data were collected using the Coolidge Executive Function Inventory (2002), the Autism Social Skills Profile by Bellini and Hopf (2007), the Cognitive Emotion Regulation Questionnaire by Garnefski et al. (2001), and the Behavioral Inhibition/Behavioral Activation Systems Scale by Carver and White (1994). Structural equation modeling and SmartPLS software (version 3) were used to test the research hypotheses. The findings indicated that executive functions and behavioral brain activities were related both directly to the social skills of children with autism and indirectly through the mediating role of cognitive emotion regulation strategies (p < .05). The results can be utilized by centers working with children with autism and by their families to improve these children’s communication skills.